Provider Perceptions of Facilitators of and Barriers to Implementation of the Zika Contraception Access Network: A Qualitative Evaluation - Acosta-Pérez, Edna; Lathrop, Eva; Vega, Samaris; Zapata, Lauren B.; Mendoza, Zipatly; Huertas-Pagán, Xavier; Hurst, Stacey; Powell, Rachel; Romero, Lisa (Puerto Rico Health Sciences Journal, 2023)
Objective: From May 2016 through September 2017, the Zika Contraception Access Network (Z-CAN) program increased access to contraception during the Zika virus outbreak in Puerto Rico by providing no-cost client-centered contraceptive counseling and (same-day) access to the full range of US Food and Drug Administration–approved reversible contraceptives to women desirous of not becoming pregnant. The purpose of this study was to identify areas for programmatic improvement and enhance the sustainability of services from the perspectives of participating Z-CAN physicians and other staff. Methods: From April through July 2017, 49 in-depth key-informant interviews were conducted with Z-CAN physicians and clinic staff. Twenty-five clinics participating in the Z-CAN program were selected through a cluster randomization process. A semi-structured interview guide was developed to explore the participants’ perceptions of the Z-CAN program and examine facilitators of and barriers to said implementation. A thematic analysis of the emerging topics was conducted. Results: Our analysis encountered 4 common overarching themes: facilitators of the Z-CAN program; barriers to Z-CAN implementation; the perceived impact of Z-CAN on providers and communities; and the sustainability of contraception access after the Z-CAN program ended. The key findings were that provider training, mentor support, and communication campaigns facilitated program implementation and that delays in the acquisition and distribution of contraceptives were obstacles. Conclusion: Lessons learned from the implementation of Z-CAN from the perspective of physicians and other staff can be used to work towards sustainable contraceptive services in Puerto Rico and inform other contraception-access programs’ design and implementation strategies.